Delivery of medical care in an urban core - Barsky, Percy (1972)
Seventy-six families who had an annual income under $3000, and who lived within half a mile of a medical centre were interviewed in their own homes. Their attitudes and opinions towards health care delivery service, family health and medical personnel, were obtained. They were found to be well aware of the freedom of choice which they possess by virtue of their medical registration certificate and the majority chose to go to private physicians for their care. As high as 55% of the consumers were chronically afflicted. Of these, 65% made medical visits every six weeks, and 20% went weekly. Forty per cent made well-care visits, and only 5% received no care at all. The data demonstrate a degree of satisfaction with, and acceptance of, health delivery service in this specific urban area.